2012
DOI: 10.1111/j.1365-2982.2012.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Tianeptine vs amitriptyline for the treatment of irritable bowel syndrome with diarrhea: a multicenter, open‐label, non‐inferiority, randomized controlled study

Abstract: Tianeptine is not inferior to amitriptyline for treating IBS-D in terms of both efficacy and tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…There were a total of 15 publications that explicitly recorded the frequency or types of sexual function change under amitriptyline use. They included one observational study ( Couper-Smartt & Rodham, 1973 ), one review study ( Montgomery, 1995 ), eight randomized case-control or case-placebo clinical trials ( Bremner, 1995 ; Hekimian, Friedhoff, & Deever, 1978 ; Mathur, Sharma, Choudhary, & Jain, 2005 ; Reimherr et al, 1990 ; Sohn et al, 2012 ; Stahl, Zivkov, Reimitz, Panagides, & Hoff, 1997 ; van Ophoven, Pokupic, Heinecke, & Hertle, 2004 ; Zivkov & de Jongh, 1995 ), and five clinical case reports ( Lucca, Ramesh, Ram, Kurian, & Mathew, 2016 ; Mitchell & Popkin, 1983 ; Nininger, 1978 ; Rao, Morriss, & Michael, 1998 ; Simpson et al, 1965 ). The review study, which included pooled clinical and preclinical trials of mirtazapine (Org 3770) in Europe and the United States before 1995, was discarded from this study as the demographic information was not fully described and part of the data has been published in another study ( Montgomery, 1995 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a total of 15 publications that explicitly recorded the frequency or types of sexual function change under amitriptyline use. They included one observational study ( Couper-Smartt & Rodham, 1973 ), one review study ( Montgomery, 1995 ), eight randomized case-control or case-placebo clinical trials ( Bremner, 1995 ; Hekimian, Friedhoff, & Deever, 1978 ; Mathur, Sharma, Choudhary, & Jain, 2005 ; Reimherr et al, 1990 ; Sohn et al, 2012 ; Stahl, Zivkov, Reimitz, Panagides, & Hoff, 1997 ; van Ophoven, Pokupic, Heinecke, & Hertle, 2004 ; Zivkov & de Jongh, 1995 ), and five clinical case reports ( Lucca, Ramesh, Ram, Kurian, & Mathew, 2016 ; Mitchell & Popkin, 1983 ; Nininger, 1978 ; Rao, Morriss, & Michael, 1998 ; Simpson et al, 1965 ). The review study, which included pooled clinical and preclinical trials of mirtazapine (Org 3770) in Europe and the United States before 1995, was discarded from this study as the demographic information was not fully described and part of the data has been published in another study ( Montgomery, 1995 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the eight randomized clinical trials, the quality was considered good in four trials ( Reimherr et al, 1990 ; Sohn et al, 2012 ; Stahl, Zivkov, Reimitz, Panagides, & Hoff, 1997 ; Zivkov & de Jongh, 1995 ) due to a prospective design, a high follow-up rate (> 80%), an adequate number of patients and controls (100-200 subjects in each group), a clear main outcome and a rational methodology for sexual and clinical assessment (LOE: IIb). In another four trials ( Bremner, 1995 ; Hekimian et al, 1978 ; Mathur et al, 2005 ; van Ophoven et al, 2004 ), the design, follow-up rate, outcome and methodology were similar except for a modest number of patients and controls (less than 100 subjects in either group) (LOE: IIIb).…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-eight percent in the tianeptine compared to 66 % in the amitriptyline group reported relief of global symptoms of IBS. Further, side effects of dry mouth and drowsiness were fewer in the tianeptine group compared to amitriptyline [30].…”
Section: Traditional Medications For Abdominal Pain In Ibs-dmentioning
confidence: 91%
“…116 In addition, SSRIs did not improve abdominal pain or enhance the QOL of the IBS patients. SSRIs promote peristalsis and thus are considered to be more effective for IBS-C than IBS-D. 117 A recent study in Korea reported that the selective 5-HT reuptake enhancer tianeptine was not inferior to the TCA amitriptyline in providing global relief of IBS symptoms (abdominal pain/ discomfort, stool frequency/consistency, QOL, and overall treatment satisfaction) in patients with IBS D. 121 Therefore, SSRIs may provide some degree of symptom relief in a subset of patients with IBS. SSRIs are more tolerable and have fewer side effects compared with TCAs, and the risk of critical adverse events is minimal.…”
Section: • Grade Of Recommendation: 2 • Level Of Evidence: B • Not Vomentioning
confidence: 99%